Crystal of naphthalene derivative

By finding that the crystalline morphology of KUS121 dihydrate has excellent storage stability and the corresponding method was prepared, the problem of low storage stability of KUS121 crystals was solved, and stable preparation and storage of raw materials was achieved.

CN119816485APending Publication Date: 2025-04-11KYOTO DRUG DISCOVERY & DEV CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380065973.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-27
Filing Date
2023-10-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The storage stability of KUS121 crystals is not high, and the tendency of decreasing crystallinity, collapse of crystal morphology, and increase of water content is significant, resulting in difficulty in drug quality control.

Method used

The crystalline morphology of the KUS121 dihydrate was found to have excellent storage stability, and a method for preparing the crystal was prepared, including dissolving KUS121 in an aqueous solvent under appropriate heating, cooling the precipitation of the crystals, and drying under specific humidity and temperature conditions.

Benefits of technology

The high storage stability of the KUS121 dihydrate crystal is achieved, making it useful as a stable raw material, and stability and reproducibility are ensured by the preparation method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention relates to a novel crystal of KUS121 useful as a medicament and a method for preparing said crystal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a novel crystal of KUS121 which can be used as a medicine and a method for preparing the crystal. Background Art

[0002] Sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate (hereinafter also referred to as "KUS121") is a compound having a naphthalene structure, which has been developed as a drug for treating central retinal artery occlusion (Patent Document 1). KUS121 is dissolved for topical administration as an injection. For the API used for manufacturing, before its preparation, it is usually stored as a crystalline API, which is generally believed to have excellent storage stability and is controlled in terms of quality. This is because the API needs to reach its high quality at this stage and needs to be stored for a certain period of time.

[0003] However, the storage stability of KUS121 crystals is not always high, for example, under normal accelerated test conditions, the tendency of decreased crystallinity, collapse of crystal morphology, and increased water content is significant. Therefore, from the perspective of drug quality control, it is necessary to store crystals under more stringent storage conditions than usual. In addition, multiple crystal forms have been identified as KUS121 APIs, and therefore it is necessary to prepare a single crystal form with ideal stability and also establish such a stabilization method.

[0004] As mentioned above, there is a need to find a more stable crystal of KUS121 drug substance and also to establish a method that can stably prepare such a stable single crystal form with good reproducibility. Prior art

[0005] (Patent Document)

[0006] [Patent Document 1] WO 2012 / 014994 Summary of the invention

[0007] (Technical Issues)

[0008] The object of the present invention is to find a stable crystal of KUS121 as an industrial bulk drug and to establish a method thereof.

[0009] (Solution to the problem)

[0010] The inventors first started the research on the crystal form of KUS121 to solve the above problems, and found that there were up to 20 types of crystal polymorphs only in those studies. The inventors further analyzed and then found that these crystal polymorphs included some solvates containing solvents used in the crystallization process, and also included some types of hydrates. After further research, the inventors finally found that one of the crystalline forms of KUS121 dihydrate had particularly excellent storage stability, and established a method for preparing only the dihydrate crystalline form. Based on these new discoveries, the present invention has been completed.

[0011] The present invention includes the following embodiments.

[0012] (Article 1)

[0013] A crystal of sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate dihydrate, characterized in that the X-ray powder diffraction pattern has at least four diffraction angles (2θ°±0.5°) peaks selected from 6.9°, 13.3°, 14.2°, 15.0°, 17.1°, 18.5°, 19.6°, 21.1°, 22.9°, 23.7°, 26.7°, 27.4°, 29.5°, 34.1° and 36.1°.

[0014] (Article 2)

[0015] A crystal of sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate dihydrate, characterized in that the X-ray powder diffraction pattern has at least four diffraction angles (2θ°±0.2°) peaks selected from 6.9°, 13.3°, 14.2°, 15.0°, 17.1°, 18.5°, 19.6°, 21.1°, 22.9°, 23.7°, 26.7°, 27.4°, 29.5°, 34.1° and 36.1°.

[0016] (Article 3)

[0017] The crystal according to Item 1 or 2, wherein the selected diffraction angle peaks are at least five peaks.

[0018] (Article 4)

[0019] The crystal according to Item 1 or 2, wherein the selected diffraction angle peaks are at least 10 peaks.

[0020] (Article 5)

[0021] The crystal according to clause 3, wherein the selected diffraction angle peaks are 6.9°, 13.3°, 14.2°, 15.0° and 17.1°.

[0022] (Article 6)

[0023] The crystal according to clause 4, wherein the selected diffraction angle peaks are 6.9°, 13.3°, 14.2°, 15.0°, 17.1°, 19.6°, 21.1°, 26.7°, 27.4° and 29.5°.

[0024] (Article 7)

[0025] A method for preparing a crystal of sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate dihydrate, the method comprising

[0026] (i) dissolving KUS121 in an aqueous solvent, which is a solvent commonly used in pharmaceutical manufacturing, under appropriate heating, and stirring the solution at 40° C. to 100° C.;

[0027] (ii) gradually cooling the solution to precipitate crystals, and collecting the precipitated crystals on a filter, and

[0028] (iii) drying the crystals at a temperature of 30° C. to 70° C. in an atmosphere of relative humidity of 10% RH to 100% RH to obtain crystals of sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate dihydrate.

[0029] (Article 8)

[0030] A method for preparing a crystal of sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate dihydrate, the method comprising

[0031] (i) dissolving KUS121 at a concentration of 1% (w / v) to 20% (w / v) in an aqueous solvent, which is a solvent commonly used in pharmaceutical manufacturing, under appropriate heating, and stirring the solution at 40° C. to 100° C. for more than 5 min,

[0032] (ii) cooling the solution to -20°C to 30°C at a cooling rate of 0.01°C / min to 1°C / min, and collecting the precipitated crystals on a filter, and

[0033] (iii) drying the crystals at a temperature of 30° C. to 70° C. in an atmosphere of relative humidity of 10% RH to 100% RH to obtain crystals of sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate dihydrate.

[0034] (Article 9)

[0035] The method according to item 7 or 8, wherein the commonly used solvent is an alcohol solvent.

[0036] (Article 10)

[0037] The process according to item 9, wherein the alcohol solvent is methanol, ethanol, 1-propanol and / or 2-propanol.

[0038] (Article 11)

[0039] A method according to any one of clauses 7 to 10, wherein the drying step in (iii) is carried out at normal pressure for more than 10 hours.

[0040] (Article 12)

[0041] A method according to any one of clauses 7 to 10, wherein the drying step in (iii) is carried out in a drying chamber in which a tray filled with water is placed at a temperature of 30°C to 50°C and a pressure of 2 kPa to 5 kPa for more than 10 hours.

[0042] (Article 13)

[0043] A method according to any one of clauses 7 to 10, wherein the drying step in (iii) is carried out in a drying chamber at a temperature of 30°C to 50°C and a pressure of 1 kPa to 7 kPa for more than 5 hours while blowing nitrogen saturated with water vapor into the drying chamber.

[0044] (Effects of the Invention)

[0045] The crystal of KUS121 dihydrate of the present invention is a crystalline form having excellent storage stability among many other crystalline polymorphs of KUS121, and can be used as a stable API in manufacturing. In addition, the method for preparing the crystal of KUS121 dihydrate established by the present invention makes it possible to stably prepare the crystal of KUS121 dihydrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 The X-ray powder diffraction pattern of the dried KUS121 dihydrate crystals in the examples is shown.

[0047] Figure 2 The results of differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) of the dried crystals of KUS121 dihydrate in Examples are shown.

[0048] Figure 3 The Raman scattering spectrum (FT-Raman) of the dried KUS121 dihydrate crystals in the examples is shown.

[0049] Figure 4 A micrograph (PLM) of crystals of KUS121 dihydrate after drying in Examples is shown.

[0050] Figure 5 The X-ray powder diffraction pattern of the crystals of KUS121 anhydrate in Examples is shown.

[0051] Figure 6 The X-ray powder diffraction pattern of the crystals of KUS121 monohydrate in Examples is shown.

[0052] Figure 7 The results of differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) of the crystals of KUS121 monohydrate in Examples are shown.

[0053] Figure 8 The X-ray powder diffraction pattern of the crystal of KUS121 tetrahydrate in the Examples is shown.

[0054] Fig. 9 The results of differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) of the crystals of KUS121 tetrahydrate in Examples are shown. DETAILED DESCRIPTION

[0055] The compound of the present invention, sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate (KUS121), has the structure shown below, and its production method and spectral data are disclosed in Patent Document 1.

[0056]

[0057] In the present invention, the crystalline material can be analyzed using conventional techniques, such as X-ray powder diffraction (XRPD), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), Raman scattering spectroscopy (FT-Raman) and photomicrographs (PLM).

[0058] The 2θ values ​​of X-ray powder diffraction patterns may be slightly different between instruments or between samples, so the numbers described herein are not absolute. In general, the measurement error of the diffraction angle in the X-ray powder diffraction spectrum is, for example, about ± 0.2 ° (in 2θ), and this degree of measurement error should be considered when analyzing X-ray powder diffraction data. In addition, in the present invention, the value of the diffraction angle of the crystal of KUS121 dihydrate varies greatly between measuring instruments, so the measurement error of the diffraction angle is even greater, for example, about ± 0.5 ° (in 2θ) should be considered. In addition, intensity can vary according to experimental conditions and sample preparation (preferred orientation). In the present invention, the values ​​obtained by measuring using copper radiation (Cu Kα, 45 kV / 20 mA, λ=1.5418 Å) are shown.

[0059] Preparation of KUS121 dihydrate crystals

[0060] The method for preparing crystals of sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate dihydrate is characterized by comprising: (i) dissolving KUS121 in an aqueous solvent, which is a solvent commonly used in pharmaceutical manufacturing, under appropriate heating, and stirring the solution under heating; (ii) cooling the heated solution to precipitate crystals, and collecting the wet crystals on a filter, and (iii) drying the wet crystals.

[0061] Preferably, by adding seed crystals in step (ii), the reliability of controlling the formation of crystals of KUS121 dihydrate can be improved.

[0062] The "solvent is a solvent commonly used in the manufacture of pharmaceuticals" defined in the above step (i) is not particularly limited as long as it is a solvent commonly used in the manufacture of pharmaceuticals, and includes, for example, alcohol solvents such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methoxyethanol, 1-methoxy-2-propanol, 2-methyl-1-propanol, 3-methyl-1-butanol and 1-pentanol; and other solvents commonly used in the manufacture of pharmaceuticals such as acetone, anisole, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, tert-butyl methyl ether, dimethyl sulfoxide, diethyl ether, ethyl formate, heptane, methyl ethyl ketone, methyl isobutyl ketone, pentane, nitromethane, acetonitrile, acetone, 4-methoxy-2-pentanone, 1,2-dimethoxyethane, toluene, pyridine, tetrahydrofuran, cyclohexane, heptane and bis(2-methoxyethyl) ether. In addition, it includes a mixed solvent of the above-mentioned solvents, or a mixed solvent of these solvents and other solvents. Preferably, it includes methanol, ethanol and 2-propanol, and more preferably ethanol.

[0063] The water content of the "aqueous solvent commonly used in pharmaceutical manufacturing" depends on the type of solvent used, but it is generally 5% to 90%; and preferably 10% to 50% for methanol, 10% to 90% (more preferably 10% to 60%) for ethanol, and about 30% for 2-propanol.

[0064] The concentration of KUS121 dissolved in the aqueous solvent in the above step (i) may be 1% (w / v) to 20% (w / v), preferably 2% (w / v) to 10% (w / v).

[0065] The heating temperature in the above step (i) depends on the type of solvent used, but it may be 40 to 100°C, preferably 50 to 80°C, more preferably 60 to 80°C.

[0066] The stirring time in the above step (i) is not particularly limited as long as KUS121 is sufficiently dissolved, and is generally 5 minutes or more, preferably 10 minutes or more.

[0067] The cooling rate in the above step (ii) is usually 0.01 to 1° C. / min, preferably 0.05 to 0.5° C. / min. And the cooling is usually carried out to -20 to 30° C., preferably to 0 to 30° C. After reaching these temperatures, stirring is usually continued until the crystals are mature (age), or stirring is stopped and allowed to stand.

[0068] Regarding the drying conditions in the above step (iii), the drying is usually carried out at a temperature of 30°C to 70°C in an atmosphere with a relative humidity of 10% RH to 100% RH, preferably at a temperature of 30°C to 60°C in an atmosphere with a relative humidity of 30% RH to 95% RH, and more preferably at a temperature of 40°C to 60°C in an atmosphere with a relative humidity of 40% RH to 70% RH. The drying time is usually 3 hours or more, preferably 10 hours or more. And the drying can be carried out under the condition of blowing in air appropriately.

[0069] In addition, drying can be carried out under appropriate reduced pressure. The pressure under reduced pressure is generally 0.05 kPa to 20 kPa, preferably 1 kPa to 20 kPa. The temperature under reduced pressure is generally 30°C to 60°C, preferably 30°C to 50°C, and the humidity can be controlled by placing a tray filled with water in the drying chamber or by blowing nitrogen containing water vapor. A preferred embodiment under reduced pressure is to dry for more than 5 hours at 30°C to 50°C and under a pressure of 1 kPa to 7kPa while blowing nitrogen saturated with water vapor into the drying chamber. Another preferred embodiment under reduced pressure is to dry for more than 10 hours at 30°C to 50°C and under a pressure of 2 kPa to 5 kPa in a drying chamber where a tray filled with water is placed.

[0070] Example

[0071] The present invention is further explained in detail below by the following examples, but these are not intended to limit the present invention.

[0072] (1) Analysis method

[0073] Each of the prepared crystals was analyzed using the following analytical method under the conditions described therein.

[0074] X-ray powder diffraction (XRPD)

[0075] (Measurement condition 1)

[0076] X-ray powder diffraction data were acquired using a PhotonMax high-throughput 9 kW rotating cathode X-ray generator (SmartLab 9 kW, Rigaku). All diffraction patterns were acquired using copper radiation (CuKα, 45 kV / 200 mA, λ = 1.5418 Å) and using a Kβ filter to reduce unnecessary radiation. The measurement was performed by placing the sample lightly crushed in an agate mortar on the measurement stage and then scanning the sample under 2θ scanning conditions, with a scanning range of 3° to 40°, a scanning speed of 20° / min, and a step size of 0.02°.

[0077] (Measurement condition 2)

[0078] X-ray powder diffraction data were acquired on Si zero-background wafers using a diffractometer (X'PertPro, PANalytical). Copper radiation (CuKα, 45 kV / 40 mA, λ = 1.5418 Å) and X'celerator TMRTMS (real-time multi-strip) detector and use nickel filter to reduce unnecessary radiation, obtain all diffraction patterns. Scanning is carried out at 2θ, and wherein scanning range is 2 ° to 40 ° and step length is 0.02 °. The configuration on the input beam side is composed of fixed divergence slit (1 / 4 °), 0.04 radian Soller slit, anti-scatter slit (1 / 4 °) and 10 mm beam mask. The configuration on the diffraction beam side is composed of fixed divergence slit (1 / 4 °) and 0.04 radian Soller slit.

[0079] (Measurement condition 3)

[0080] X-ray powder diffraction data were obtained using a diffractometer (MiniFlex 600, Rigaku). All diffraction patterns were obtained using copper radiation (CuKα, 40 kV / 15 mA, λ = 1.5418 Å) and a Kβ filter was used to reduce unnecessary radiation. Scanning was performed at 2θ with a scan range of 5° to 50°, a scan speed of 5° / min, and a step size of 0.02°.

[0081] Differential Scanning Calorimetry (DSC)

[0082] Differential scanning calorimetry was performed using a differential scanning calorimeter (TA Instruments Q100 or Q2000, TA Instruments) equipped with an autosampler and a refrigerated cooling system. DSC thermograms were obtained by placing about 1 mg to 10 mg of solid sample in a corrugated aluminum pan and heating it at 10°C / min or 15°C / min under a N2 purge of 40 mL / min.

[0083] Thermogravimetric analysis (TGA)

[0084] Thermogravimetric analysis was performed using a thermogravimetric analyzer (TA Instruments Q50 or Q500, TA Instruments). TGA thermograms were obtained by placing about 1 mg to 10 mg of solid sample in an aluminum pan and heating it at 10°C / min or 15°C / min under a 40 mL / min N2 purge.

[0085] Raman scattering spectroscopy (FT-Raman)

[0086] Raman spectra were measured using a Raman instrument (Nicolet NXR9650 or NXR960 spectrometer, Thermo Electron) equipped with a 1064 nm Nd:YVO4 excitation laser, InGaAs and liquid nitrogen cooled Ge detectors and MicroStage. All spectra were acquired at 4 cm-1 resolution and 64 to 1024 scans using a Happ-Genzel apodization function and two-stage zero filling. A neutral density filter (1.0 optical density) was used if detector saturation was observed.

[0087] Micrograph (PLM)

[0088] Micrographs were taken using a BX60 polarizing microscope (Olympus) equipped with an Olympus DP70 camera.

[0089] Moisture measurement

[0090] The water content of each crystal was measured using one of the following three methods.

[0091] (Measurement of water content in crystals of KUS121 anhydrate)

[0092] The water content was measured using a coulometric moisture meter (CA-100, Nitto Seiko Analytech) using about 0.5 g of a solid sample, Aquamicron GEX as a solvent, and 3 mg of Aquamicron SS as a titrant.

[0093] (Measurement of water content of KUS121 dihydrate crystals)

[0094] The water content was measured using a Karl Fischer moisture meter (AQUACOUNTER AQV-2100, HIRANUMA) equipped with an electrolytic cell stirrer for iodine generation and a constant current potentiometer, using about 0.2 g of a solid sample, Aquamicron GEX as a solvent, and 3 mg of Aquamicron SS-Z as a titrant.

[0095] (Measurement of water content of KUS121 monohydrate and tetrahydrate crystals)

[0096] The water content was calculated from the DSC thermogram measured using differential scanning calorimetry (differential scanning calorimeter TA Instruments Q100 or Q2000, TA Instruments) and the TGA thermogram measured using thermogravimetric analysis (thermogravimetric analyzer TA Instruments Q50 or Q500, TA Instruments). The measurement was performed in the following manner: about 1 mg to 10 mg of a solid sample was placed in an aluminum pan and heated at 10° C. / min or 15° C. / min under a N2 purge of 40 mL / min.

[0097] (2) Crystal preparation

[0098] Crystals of KUS121 dihydrate, anhydrate, monohydrate and tetrahydrate were prepared according to the following procedure. And the drying process for the dihydrate crystals was performed in the following two ways: under normal pressure and under reduced pressure.

[0099] Preparation of dihydrate crystals (crystallization)

[0100] 90% ethanol aqueous solution (120 mL) was added to KUS121 (5.00 g), and the mixture was stirred to dissolve at more than 67 ° C. The solution was filtered while hot, and the container and filter were washed with 90% ethanol aqueous solution (5 mL), and the washing solution was also filtered. The filtrate was heated to more than 67 ° C, stirred for 30 minutes, and cooled to 60 ° C at a cooling rate of 0.1 ° C / min. The cooled solution was stirred at 60 ° C for one hour to ripen the crystals, and cooled to 22 ° C at a cooling rate of 0.05 to 0.5 ° C / min. The precipitated crystals were collected on the filter, and washed with 90% ethanol aqueous solution (5 mL) to obtain wet crystals of KUS121 dihydrate (net yield: 97.3%).

[0101] Water content: 13.0%

[0102] Preparation of dihydrate crystals (drying at normal pressure)

[0103] Wet crystals of KUS121 dihydrate prepared by the above procedure (24.0 g, net 17.4 g) were dried at 50° C. with blowing of air to obtain dry crystals of KUS121 dihydrate (yield: 91.7%).

[0104] Water content: 7.4%

[0105] Preparation of dihydrate crystals (vacuum drying)

[0106] The wet crystals (2.32 kg) of KUS121 dihydrate prepared by the above procedure were spread over two buckets, and the buckets were placed on a rack in a vacuum dryer together with a beaker filled with distilled water (4.56 g). Drying was performed under reduced pressure for about 16 hours while the external temperature of the dryer was controlled to 35° C. and the vacuum degree was controlled to 2.86 to 2.96 kPa to obtain 1.92 kg of dried crystals of KUS121 dihydrate.

[0107] Water content: 7.7%

[0108] Analysis results of dried dihydrate crystals

[0109] X-ray powder diffraction (measurement conditions 1, see Figure 1 )(2θ): 6.9°, 13.3°, 14.2°, 15.0°, 17.1°, 18.5°, 19.6°, 21.1°, 22.9°, 23.7°, 26.7°, 27.4°, 29.5°, 34.1°, 36.1°

[0110] Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA): See Figure 2

[0111] Raman scattering spectroscopy (FT-Raman): see Figure 3

[0112] Micrograph (PLM): see Figure 4

[0113] Preparation of anhydrate crystals

[0114] KUS121 (71.8 g) and ethanol (5840 g) are placed in a flask, and the mixture is stirred at 76°C to 77°C (reflux) for 30 minutes to dissolve. Under agitation, the mixture is cooled to 65°C to 70°C, and filtered while hot to remove insoluble matter. The operation is repeated in three batches, and the filtrate is merged into one batch. Under agitation, the mixture is cooled to 27°C using a water bath, and is further cooled to 4°C using an ice bath. Under agitation, the precipitated solid is matured at 3°C ​​to 4°C for one hour, and mature crystals are collected on a filter, and washed three times with 292 g of ethanol. The crystal is dried under reduced pressure at 30°C to 80°C for 61 hours, to obtain the crystal (yield: 54.8%) of KUS121 anhydrous.

[0115] Water content: 2.3%.

[0116] X-ray powder diffraction (measurement conditions 3, see Figure 5)(2θ): 7.2°, 13.2°, 15.4°, 16.2°, 17.5°, 20.0°, 22.6°, 25.9°, 27.3°

[0117] Preparation of monohydrate crystals

[0118] The crystals of KUS121 dihydrate (67 mg) obtained in the above procedure were dried under reduced pressure (17 in terms of Hg, 40° C.) with blowing of dry nitrogen to obtain crystals of KUS121 monohydrate (yield: 100%).

[0119] Water content: 3.4%

[0120] X-ray powder diffraction (analysis conditions 2, see Figure 6 )(2θ): 10.1°, 10.9°, 13.2°, 15.2°, 20.4°, 23.1°, 23.8°, 26.4°, 29.6°, 30.6°

[0121] Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA): See Figure 7

[0122] Preparation of tetrahydrate crystals

[0123] KUS121 (250 mg) was dissolved in 40% ethanol (2.5 mL) at 67 ° C. The solution was cooled to 60 ° C at a cooling rate of 0.1 ° C / min, and stirred for one hour. Further, the solution was cooled to 55 ° C at a cooling rate of 0.1 ° C / min, and stirred for one hour to precipitate crystals. The suspension was cooled to 22 ° C at a cooling rate of 0.1 ° C / min, and stirred overnight. The precipitated crystals were suction filtered and dried for one hour under the condition of blowing air to obtain crystals of KUS121 tetrahydrate (yield: 74%).

[0124] Water content: 13.9%

[0125] X-ray powder diffraction (analysis conditions 2, see Figure 8 )(2θ): 6.9°, 12.5°, 13.0°, 14.4°, 16.3°, 18.8°, 21.5°, 23.5°, 24.3°, 25.1°

[0126] Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA): See Fig. 9

[0127] (3) Stability test

[0128] The crystals of KUS121 dihydrate were subjected to normal storage stability test (25°C / 60% RH, 18 months) and storage stability test under accelerated test conditions (40°C / 75% RH, 6 months). For comparison, the crystals of KUS121 anhydrate were also subjected to storage stability test under accelerated test conditions (40°C / 75% RH, 6 months) and storage stability test under normal temperature conditions (30 months). The results are shown in the table below.

[0129] In addition, the crystals of KUS121 monohydrate and the crystals of KUS121 tetrahydrate were also subjected to storage stability observation. The results are also shown in the following table.

[0130]

[0131]

[0132]

[0133] As mentioned above, the dihydrate crystals have better storage stability than other hydrate crystals and are extremely stable even under accelerated test conditions.

Claims

1. A crystal of sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate dihydrate, characterized in that: The X-ray powder diffraction pattern has at least four diffraction angles (2θ°±0.5°) peaks selected from 6.9°, 13.3°, 14.2°, 15.0°, 17.1°, 18.5°, 19.6°, 21.1°, 22.9°, 23.7°, 26.7°, 27.4°, 29.5°, 34.1° and 36.1°.

2. A crystal of sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate dihydrate, characterized in that: The X-ray powder diffraction pattern has at least four diffraction angles (2θ°±0.2°) peaks selected from 6.9°, 13.3°, 14.2°, 15.0°, 17.1°, 18.5°, 19.6°, 21.1°, 22.9°, 23.7°, 26.7°, 27.4°, 29.5°, 34.1° and 36.1°.

3. The crystal according to claim 1 or 2, wherein the selected diffraction angle peaks are at least five peaks. The crystal according to claim 1 , wherein the selected diffraction angle peaks are at least 10 peaks.

5. The crystal according to claim 3, wherein the selected diffraction angle peaks are 6.9°, 13.3°, 14.2°, 15.0° and 17.1°.

6. The crystal according to claim 4, wherein the selected diffraction angle peaks are 6.9°, 13.3°, 14.2°, 15.0°, 17.1°, 19.6°, 21.1°, 26.7°, 27.4° and 29.5°.

7. A method for preparing a crystal of sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate dihydrate, the method comprising (i) dissolving KUS121 in an aqueous solvent, which is a solvent commonly used in pharmaceutical manufacturing, under appropriate heating, and stirring the solution at 40° C. to 100° C.; (ii) gradually cooling the solution to precipitate crystals, and collecting the precipitated crystals on a filter, and (iii) drying the crystals at a temperature of 30° C. to 70° C. in an atmosphere having a relative humidity of 10% RH to 100% RH to obtain crystals of sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate dihydrate.

8. A method for preparing a crystal of sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate dihydrate, the method comprising (i) dissolving KUS121 in a concentration of 1% (w / v) to 20% (w / v) in an aqueous solvent, which is a solvent commonly used in pharmaceutical manufacturing, under appropriate heating, and stirring the solution at 40° C. to 100° C. for more than 5 min; (ii) cooling the solution to -20°C to 30°C at a cooling rate of 0.01°C / min to 1°C / min, and collecting the precipitated crystals on a filter, and (iii) drying the crystals at a temperature of 30° C. to 70° C. in an atmosphere having a relative humidity of 10% RH to 100% RH to obtain crystals of sodium 4-amino-3-[6-(4-fluoro-2-methylphenyl)pyridin-3-ylazo]naphthalene-1-sulfonate dihydrate.

9. The method according to claim 7 or 8, wherein the commonly used solvent is an alcohol solvent.

10. The method according to claim 9, wherein the alcohol solvent is methanol, ethanol, 1-propanol and / or 2-propanol.

11. The method according to any one of claims 7 to 10, wherein the drying step in (iii) is carried out at normal pressure for more than 10 hours.

12. The method according to any one of claims 7 to 10, wherein the drying step in (iii) is performed in a drying chamber in which a tray filled with water is placed at a temperature of 30 to 50°C and a pressure of 2 to 5 kPa for 10 hours or more.

13. The method according to any one of claims 7 to 10, wherein the drying step in (iii) is performed in the drying chamber at a temperature of 30 to 50°C and a pressure of 1 to 7 kPa for 5 hours or more while blowing nitrogen saturated with water vapor into the drying chamber.

Citation Information

Patent Citations

  • Naphthalene derivative

    WO2012014994A1